I see/you mean a novel - Lippard, Lucy R. 1937- (New Documents, 2021)
An experimental novel about mirrors, maps, relationships, about the ocean, elusive success and possible happiness. Weaving overeard dialogue, sexual encounters, and elements from the I Ching, Tarot, and palmistry, Lippard charts changing relationships among four people. Written in 1970, this novel brings to life political, feminist and aesthetic struggles of its time
Keywords: Artists' books; Experimental fiction, American; 20th century; Experimental fiction, American / 20th century